Rotavirus-Mediated Prostaglandin E2 Production in MA104 Cells Promotes Virus Attachment and Internalisation, Resulting in an Increased Viral Load - Sander, Willem J.; Kemp, Gabré; Hugo, Arnold; Pohl, Carolina H.; O’Neill, Hester G. (Frontiers in Physiology, 2022)
Rotaviruses are one of the leading causes of severe dehydrating diarrhoea in infants and children under the age of five. Despite the introduction of vaccines, disease burden remains high in sub-Saharan Africa, with no known anti-viral treatments available. During early infection rotavirus attaches to several cellular receptors and enters the cells by either clathrin-dependent or -independent endocytosis. Prostaglandin E2, an abundant eicosanoid, is produced from arachidonic acid during rotavirus infection and inhibition of prostaglandin E2 has a deleterious effect on rotavirus infection. In this study, MA104 cells were supplemented with γ-linolenic acid, a precursor of arachidonic acid. Infection of supplemented cells with rotavirus SA11 led to a depletion in the relative percentages of γ-linolenic acid and arachidonic acid which coincided with an increased production of prostaglandin E2 as monitored by ELISA. Confocal microscopy demonstrated that prostaglandin E2 co-localises with the viroplasm-forming proteins, NSP5 and NSP2. Due to the known association of viroplasms with lipid droplets and the fact that lipid droplets are sites for prostaglandin E2 production, our results indicate a possible role for viroplasms in the production of rotavirus-induced prostaglandin E2. Replication kinetics showed that inhibitors, targeting the biosynthesis of prostaglandin E2, had negative effects on rotavirus yield, especially during the early stages of infection. Using flow cytometry and prostaglandin E2 addback experiments, we show that prostaglandin E2 enhances the attachment and internalisation of rotavirus in MA104 cells indicating a possible role for prostaglandin E2 during clathrin-mediated rotavirus entry. The production of prostaglandin E2 during rotavirus infection could serve as a possible target for anti-viral treatment.